Writing reconstruction : race, gender, and citizenship in the postwar south - Kennedy-Nolle, Sharon D. (Gender and American culture, 2015)
After the Civil War, the south was divided into five military districts occupied by Union forces. Out of these regions, a remarkable group of writers emerged. Experiencing the long-lasting ramifications of Reconstruction firsthand, many of these writers sought to translate the era's promise into practice. Sharon D. Kennedy-Nolle blends literary history with archival research to assess the significance of Reconstruction literature as a genre.